Role of effective working capital management on financial performance of business: An empirical study of executives’ opinion (International Journal of Food and Nutritional Sciences, 2022)
According to the available empirical evidence, working capital management (WCM) has an effect on the financial performance of businesses. The impact of the environment, resources, and managerial capacity on the link between WCM and financial performance is investigated in this research using a contingency theory approach. Our sample is comprised of 802 companies that were listed on the London Stock Exchange (LSE) between 2004 and 2014. We estimated the association using a series of interactive models in a dynamic panel data analysis. The research indicates that several external factors, including the firm's environment, resources, and managerial skills, influence the effect of WCM on financial success. These results are noteworthy because they show, for the first time, how variables like the firm's environment, resources, and managerial skills impact the firm's capacity to improve performance by investing in working capital. Our findings are significant because they demonstrate how contingency theory sheds light on the circumstances in which working capital investments might improve financial performance, as well as the pertinent contingencies.